Towards a Generalized Tidal Turbine Wake Analytical Model for Turbine Placement in Array Accounting for Added Turbulence - Kabir Bashir Shariff; Sylvain S. Guillou (Energies)
This study seeks to establish a comprehensive model for estimating both the velocity deficit and turbulence intensity within a tidal turbine farm across various layout configurations. The model incorporates a spectrum of ambient turbulence intensity ranging from 5% to 20%, a rotor diameter-to-depth ratio between 20% and 60%, and a rotor thrust coefficient that varies from 0.64 to 0.98. The influence of added turbulence is factored into the evaluation of the velocity deficit within the farm. Consistent with findings from prior research, the results indicate that in a tidal farm consisting of 16 turbines, a staggered array configuration yields 21% more power compared to a rectilinear array. This staggered setup benefits from enhanced flow acceleration and greater spacing between turbines, which facilitates improved wake recovery. The findings suggest that the farm’s dimensions can be optimized by reducing lateral spacing in the rectilinear array and longitudinal spacing in the staggered array without compromising efficiency. Such reductions in farm size can lead to decreased cable expenses and create opportunities for future expansion. For the tidal turbines in shallow water regions, the ratio of rotor diameter to depth is shown to affect the power generated by the turbines. The power produced in the farm decreases with an increase in the rotor diameter-to-depth ratio due to the limited wake expansion along the vertical plane. The efficiency of a tidal farm can be increased by high ambient turbulent intensity, sufficient turbine spacing, and low rotor diameter-to-depth ratio. These factors improve the wake recovery to allow more energy to be extracted by a downstream turbine. This low-computational model can be useful in studying the wake interaction of tidal turbine parks in different configurations.